KARAKTERISTIK MASYARAKAT DI SEKITAR DAERAH TUJUAN WISATA (Studi Kasus : Taman Wisata Mekarsari, Desa Mekarsari, Kecamatan Cileungsi, Kabupaten Bogor) - Chondro Suryono; Sudarmadji Sudarmadji; Edhi Martono; Chafid Fandeli (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2015)
This article aims to analyze the characteristics of the community around tourist sites. This research uses descriptive study where data obtained from direct interviews with sources of data and direct observation in the study site. Methods of data collection is the way researchers get the data required in the conduct of research on sources of research data. It was concluded that the characteristics of the surrounding communities with the development of attractions like Mekarsari showed the positive impact, more choice of livelihood for the inhabitants of surrounding areas such as whether they wish to be employees, as entrepreneurship, or as traders. However, these positive effects are not accompanied by increased levels of public education around the village Mekarsari. This is due to the understanding of higher education has not been considered important, and also the villagers consider that the modest education (elementary, senior high school, high school) has been able to earn money, whether as laborers, trade or wiraswasta (open stalls).Keywords: Characteristics, Public, Mekarsari parc